Unlocking the Magnetic and Half-Metallic Properties of AMY2 (A = Cu, Ag; M = Sc, Ti, V, Cr, Mn, Fe; Y = S, Se) Compounds in Chalcopyrite Structure: An Ab Initio Study for Spintronics Applications - D. Vijayalakshmi; Tholkappiyan Ramachandran; G. Jaiganesh; G. Kalpana; Fathalla Hamed (Advances in Condensed Matter Physics)
We present an investigation into the magnetism exhibited by AMY2 compounds characterized by a chalcopyrite structure, where A can be Cu or Ag, M can be Sc, Ti, V, Cr, Mn, or Fe, and Y can be either S or Se. By substituting M atoms at the Ga position of AGaY2 compounds, the magnetic properties were calculated using the full potential linearized augmented plane wave method under the generalized gradient approximation and local spin density approximation with the WIEN2K code. The obtained spin-polarized results confirmed the presence of ferromagnetic and half-metallic (HM) properties in AMY2 compounds (A = Cu, Ag; M = Ti, V, Cr, Mn; Y = S, Se), wherein the HM property is preserved through p-d hybridization of p states of Y (S, Se) atoms with d (t2g) states of M (M = Ti, V, Cr, Mn) atoms, and minimal contribution of −s states of A (A = Cu, Ag) atoms. The total magnetic moments for AMY2 compounds were calculated as 1.00, 2.00, 3.00, and 4.00 µB/f.u. for M = Ti, V, Cr, Mn, respectively. For AFeY2 compounds (A = Cu, Ag; Y = S, Se), electronic band structures for both up spin and down spin states were identical, suggesting antiferromagnetic behavior at equilibrium, while AScY2 compounds (A = Cu, Ag; Y = S, Se) exhibited nonmagnetic properties at equilibrium. Overall, the accurate HM properties of AMY2 materials suggest promising prospects for their utilization in spintronics and magnetic storage device applications.